TRENDS OF MODERNIZATION OF PSYCHOLOGISTS’ PROFESSIONAL TRAINING IN THE SYSTEM OF SPECIAL EDUCATION - Sheremet, Maria; Suprun, Mykola; Suprun, Daria; Mamicheva, Olena; Kordonets, Viktoriya; Silchenko, Viktoriya; Dmytriieva, Iryna (International Journal of Psychosocial Rehabilitation, 2020)
The conceptual foundations of the theory and practice of the professional formation of the psychologist’s personality in the system of special education are substantiated. The personal qualitative priorities of its phased implementation on competency-oriented principles of the megasystem of a holistic educational space are defined, where the competency-based approach is considered as the dominant vector of updating the content of higher education in the context of multi-level training. The methodological aspects of this professional training have been developed and the training itself has been presented as a holistic systemic phenomenon in the educational space of higher pedagogical education: the essence of the given training is considered in various ways, on the basis of which its qualitative and classification characteristics, levels and systemic and structural components are determined; the content, organizational and pedagogical conditions and criteria for assessing the levels of formation of these components are defined. The following components of psychologists’professional training are defined: professional and motivational, cognitive and competence, operational and active, productive and reflexive. It is indicated that the given structural components are interrelated, interdependent and complementary to each other. The essence of the modern technologies in higher educational institutions is determined. Theoretical paradigm is scientifically substantiated, the structural-functional, organizational-didactic model of the system of psychologists’ professional training in the field of special education is developed and tested and the dynamics of the formation of its components according to the results of the implementation of this system is highlighted. Particular attention is paid to finding and developing of the optimal set of methods of its providing, developing programs and definition of developed program’s efficiency. The prospects for further research in the context of improving the psychologists’ professional training in the field of special education are outlined.